2009
DOI: 10.1124/jpet.108.148478
|View full text |Cite
|
Sign up to set email alerts
|

Involution of Collagen-Induced Arthritis with an Angiogenesis Inhibitor, PPI-2458

Abstract: Pannus formation, in both rheumatoid arthritis (RA) and collagen-induced arthritis (CIA), is angiogenesis-dependent. PPI-2458 [(1R)-1-carbamoyl-2-methyl]-carbamic acid-(3R,3S,5S, 6R)-5-methoxy-4-[(2R,3R)-2-methyl-3-(3-methyl-but-2-enyl)oxiranyl]-1-oxaspiro(2*5)oct-6-yl ester], a new fumagillin derivative known to inhibit methionine aminopeptidase 2 (MetAP-2) and endothelial proliferation at the late G 1 phase, was evaluated in CIA rats to study its potential to involute synovitis. Arthritic syngeneic LOU rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…It was previously demonstrated that PPI-2458 has protective effects on joint swelling in the rat models of arthritis induced by collagen or PG-PS [24,28,34]. Here we expand on that work, determining how the protective effects of MetAP-2 inhibition relate to the temporal development of the multistage PG-PS model of arthritis and further elucidating a mechanistic role for MetAP-2 in the pathophysiological processes involved in joint destruction of rat experimental models of arthritis.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It was previously demonstrated that PPI-2458 has protective effects on joint swelling in the rat models of arthritis induced by collagen or PG-PS [24,28,34]. Here we expand on that work, determining how the protective effects of MetAP-2 inhibition relate to the temporal development of the multistage PG-PS model of arthritis and further elucidating a mechanistic role for MetAP-2 in the pathophysiological processes involved in joint destruction of rat experimental models of arthritis.…”
Section: Introductionmentioning
confidence: 88%
“…Antiangiogenic agents that can stem pannus formation by effectively blocking the development of a blood supply have found success in experimental models of arthritis [12,28,29]. PPI-2458 is one such antiangiogenic agent that is an orally active irreversible inhibitor of the enzyme methionine aminopeptidase type-2 (MetAP-2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This triggers growth arrest of ECs in the late G 1 phase of the cell cycle, inhibiting EC proliferation and angiogenesis without affecting inflammatory cytokine release (19,21,22) or inducing apoptosis in ECs (23). PPI-2458 has reduced toxicity and greater selectivity for angiogenesis inhibition versus inflammation as compared with another fumagillin analog, AGM-1470/TNP-470 (23,24).…”
mentioning
confidence: 99%
“…PPI-2458, [(3R,4S,5S,6R)-5-methoxy-4-[(2R,3R)-2-methyl-3-(3-methylbut-2-enyl) oxiran-2-yl]-1-oxaspiro[2.5]octan-6-yl] N-[(2R)-1-amino-3-methyl-1-oxobutan-2-yl]carbamate, differs from fumagillin in that the polyolefinic chain is replaced by a carbamoyl-linked D-valinamide moiety (Olson et al, 2003;Arico-Muendel et al, 2009). PPI-2458 has demonstrated efficacy in rodent models for non-Hodgkin lymphoma (Cooper et al, 2006), melanoma , and arthritis (Bernier et al, 2004;Bainbridge et al, 2007;Hannig et al, 2007;Lazarus et al, 2008;Brahn et al, 2009;Ashraf et al, 2010;Ashraf et al, 2011). In preclinical studies, PPI-2458 was approximately equipotent in several in vivo efficacy models by both oral and parenteral routes of administration, despite an apparently modest oral bioavailability (F% = 6) (AricoMuendel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%